Identification of Groundwater Potential using Schlumberger Array of Resistivity Method in Bulukumba, South Sulawesi - Agussalim, Agussalim; AS, Nur Ichzan (Politeknik Negeri Ujung Pandang, 2021)
The research was carried out in Bontorannu Village, Kajang District, Bulukumba Regency, South Sulawesi. The research area is a plain area with rainfed rice fields. Therefore, it is necessary to do research to identify the potential of groundwater as a source of irrigation. The purpose of this research is to provide an estimate of the plane, position, and depth of the aquifer layer in the soil based on the interpretation of measurements using the resistivity method of the Schlumberger array. Through the results of this interpretation, the pattern/contour modeling of the distribution of the aquifer layer in the soil is determined which is projected as groundwater. This research is an experimental research with a descriptive approach method. Methods of this research consists of research preparation, data acquisition, processing and interpretation of data using Res2dinv software. The measurement points were selected through feasibility survey. There are two measurement points that length of each track used is a maximum of 300 meters. The results showed that on track 1 there is a layer suspected of being a shallow aquifer with a depth of 12-22 m. While on track 2, a potential deep aquifer layer is detected with a depth of 13-25 m.